2018
DOI: 10.1142/s0219622015500170
|View full text |Cite
|
Sign up to set email alerts
|

Designing and exploring risk matrices with MACBETH

Abstract: Risk matrices are adopted and recommended by many organizations, but the way they are usually constructed violates some basic theoretical principles, giving rise to inconsistent risk ratings. This paper studies ways in which multiple criteria and portfolio decision analyses can improve the design and deployment of risk matrices, using MACBETH (the \Measuring Attractiveness by a Categorical Based Evaluation TecHnique"). Firstly, it introduces`value risk-matrices', built with MACBETH in the following modeling st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Risk matrices are easy to implement and can be implemented even where data are limited. Therefore, they have become popular decision-support tools in both the public and private sectors, (3)(4)(5)(6) in areas such as well-integrity risk, (7) drilling hazard management, (8) climatic change responses, (9) and so on. However, despite its simplicity and wide usage, recent research has revealed several flaws in the risk matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Risk matrices are easy to implement and can be implemented even where data are limited. Therefore, they have become popular decision-support tools in both the public and private sectors, (3)(4)(5)(6) in areas such as well-integrity risk, (7) drilling hazard management, (8) climatic change responses, (9) and so on. However, despite its simplicity and wide usage, recent research has revealed several flaws in the risk matrix.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the National Patient Safety Agency from the United Kingdom has recommended risk managers to use RMs in the National Health Service within an integrated system of risk assessment (National Patient Safety Agency, ) and the British Standard BS 8800:2004 for evaluating OHS risks (Technical Committee HS/1, ). Additional factors have stimulated the popularity of RMs, namely their easiness and quickness of use, their demand for little expertise (Oliveira et al., ), and their widespread incorporation in several popular software packages, such as in the Environment, Health, and Safety Risk Assessment module of SAP (SAP AG, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their extensive use, RMs have been shown to violate some theoretical principles and suffer from methodological problems (Cox, , ; Pickering and Cowley, ; Oliveira et al., ), shared by the RM in Table , such as:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations